Green-synthesized nanocatalysts and nanomaterials for water treatment: Current challenges and future perspectives - Nasrollahzadeh, Mahmoud; Sajjadi, Mohaddeseh; Iravani, Siavash; Varma, Rajender S (Journal of hazardous materials, 2021)
Numerous hazardous environmental pollutants in water bodies, both organic and inorganic, have become a critical global issue. As greener and bio-synthesized versions of nanoparticles exhibit significant promise for wastewater treatment, this review discusses trends and future prospects exploiting the sustainable applications of green-synthesized nanocatalysts and nanomaterials for the removal of contaminants and metal ions from aqueous solutions. Recent trends and challenges about these nanocatalysts and nanomaterials and their potential applications in wastewater treatment and water purification are highlighted including toxicity and biosafety issues. This review delineates the pros and cons and critical issues pertaining to the deployment of these nanomaterials endowed with their superior surface area, mechanical properties, significant chemical reactivity, and cost-effectiveness with low energy consumption, for removal of hazardous materials and contaminants from water; comprehensive coverage of these materials for industrial wastewater remediation, and their recovery is underscored by recent advancements in nanofabrication, encompassing intelligent and smart nanomaterials.
Keywords: Biogenic nanomaterials; Sustainable methods; Water treatment; Green synthesis; Nanocatalysts